PENGARUH PERCEIVED SECURITY, PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, DAN SOCIAL INFLUENCE TERHADAP ADOPTION OF E -WALLET LinkAja PADA GENERASI Y DI DKI JAKARTA - Gilbert Aryaputra Ganady; Denny Septa Haryanti (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to find out the effect of Eco Label, Eco Brand, and Environmental Advertisement on Consumer Purchase Behavior on Tessa Tissue in Bekasi City. This study uses primary data sourced from questionnaires with a total of 150 respondents that using Tessa in Bekasi City. The sampling technique that used was non-probability sampling. The data analysis technique used multiple linear regression analysis. The results show that Eco Label, Eco Brand, and Environmental Advertisement have an effect on Consumer Purchase Behavior